Penguatan Usaha Kelompok Tani Melalui Diversifikasi dan Digitalisasi Produk Unggulan di Desa Bandilan Kabupaten Bondowoso - Riniati Riniati; Agus mahardiyanto; Moehammad Fathorrazi; Anifatul Hanim; Abdul Fatah (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2026)
Bandilan Village is one of the promising villages in Bondowoso Regency that requires support in the digitalisation and diversification of products produced by the Rimba Jaya 3 farmers’ group. The marketing of MSME products, Halal certification and the scarcity of fertiliser are issues facing the village. The community service method, using a Participatory Action Research (PAR) approach, involves training sessions, consultations, mentoring and evaluation of activities involving all village stakeholders, ranging from the village head, village officials, farmer groups and the surrounding community, in producing products, including meeting Halal certification requirements. This community service initiative can serve as an alternative for the people of Bandilan, particularly the Rimba Jaya 3 Group, to address the scarcity of subsidised fertiliser and improve the marketing of flagship SME products. It also helps SMEs to develop through mentoring to obtain Halal certification. Liquid Organic Fertiliser (POC) is an alternative for farmers as a substitute for subsidised fertiliser, which is often in short supply, by utilising unused tofu waste in the village. Through support for 10 SMEs in the form of marketing and halal certification, it is hoped that SMEs in the village of Bandilan will be able to move up the ladder. A challenge that has arisen in this support programme is the limited number of young people interested in getting involved, as many of them choose to migrate to the city rather than become farmers and entrepreneurs in their own village.